THE EFFECT OF IMPLEMENTING PAIKEM USING STUDENT-CENTERED LEARNING, CASE-BASED LEARNING, AND COOPERATIVE LEARNING ON LEARNING EFFICIENCY AND EFFECTIVENESS - I Indrayati (Erudio Journal of Educational Innovation, 2019)
The learning activities of financial accounting practice in Malang State Polytechnic (also called Polinema) have not been able to generate learning results meeting the real-world needs, in respect of the cognitive, psychomotor and affective aspects. Thereby, the researcher developed a new method in the future learning: PAIKEM (which stands for Pembelajaran Aktif, Inovatif, Kreatif, Efektif dan Menyenangkan - Active, Innovative, Creative, Effective and Fun Learning) using student-centered learning, case-based learning and cooperative learning for efficiency and effectiveness of learning. The purpose of this study is to develop and apply the PAIKEM method with student-centered learning, case-based learning, and cooperative learning to generate high-quality human resources in the accounting department of Polinema for competing in global or international markets. This is explanatory research discussing the effect of teacher-centered learning, student-centered learning, project-based learning, creative learning, effective learning, and fun learning variables on the efficiency and effectiveness of learning. This research employs a population of 400 students and a sample of 180 students taken by purposive sampling with a 5-point Likert scale measurement. The data analysis method utilized multiple linear regressions. The primary data source was collected through documentation from the questionnaire. The results revealed that the project-based learning, cooperative learning, and fun learning variables had a significant effect on efficiency while the teacher-centered learning, student-centered learning, creative learning, and effective learning variables did not significantly affect learning efficiency. Furthermore, student-centered learning, cooperative learning, effective learning, and fun learning variables had a significant effect on learning effectiveness; while the teacher-centered learning, case-based learning, creative learning variables did not.